Educators in prison. Identity and learning valences embedded in the policies and organizational practices and behaviors - Francesca Torlone (Firenze University Press, 2023)
Professional identity of the legal and pedagogical professionals in prison settings has been greatly affected by transformations that have occurred over time in the culture of the penal and penitentiary system. The transition towards a re-educating culture of the prison system after the Second World War has highlighted a new identity, a new role. This is not always accompanied by new awareness and educational practices and behaviours. This paper intends to reconstruct the professional identity of the legal and pedagogical professionals and their role while working through a short normative excursus that over time accompanied its definition. The ability of professionals to construct the meaning of their educational job and role in prison is affected by the values, ethics and knowledge of each single professional. It is also affected by the social and working system they belong to. The more each professional is able to autonomously construct the sense of his/her own work and professional role, the clearer and more conscious acted his/her identity is. Explicit rules do not necessarily impact on that.   La professionalità rieducativa in carcere. Identità e valenze educative incorporate nelle policy, prassi e comportamenti organizzativi. Le trasformazioni occorse nel tempo nella cultura del sistema penale e penitenziario hanno inciso sull' identità professionale dei professionisti della funzionalità giuridico-pedagogica. Il passaggio verso una cultura rieducante del sistema-carcere nel secondo dopo-guerra ha messo in luce una nuova identità, un nuovo ruolo cui non sempre si accompagnano nuove consapevolezze e pratiche educative. Il contributo intende ricostruire l'identità di ruolo del funzionario giuridico-pedagogico attraverso un breve excursus normativo che ne ha accompagnato la definizione. Sulla capacità di costruirsi il senso del lavoro educativo in carcere incidono valori, etica, conoscenze del singolo professionista ma anche i sistemi sociali e lavorativi di appartenenza. Quanto più il professionista è in grado di costruire in autonomia il senso del proprio lavoro e del proprio ruolo professionale tanto più chiara e consapevolmente agita è la sua identità. Non è detto importi la presenza di teorie dichiarate.